Intrapartum ultrasound: viewpoint of midwives and parturient women and reproducibility - Van Adrichem A; Faes E; Kinget K; Jacquemyn Y (Dove Medical Press, 2018)
Adrielle Van Adrichem,1 Ellen Faes,1 Kristof Kinget,2 Yves Jacquemyn1 1Antwerp University Hospital UZA, Antwerp University UA – ASTARC, Edegem, Belgium; 2KLINA Hospital, Brasschaat, Belgium Introduction: Vaginal examination (VE) is known to be subjective in interpretation and is considered uncomfortable by many women. Intrapartum ultrasound aims to be more objective and less invasive. The purpose of this study was to evaluate the acceptability of introducing intrapartum ultrasound to both midwives and parturients. Furthermore, we wanted to evaluate the reproducibility of different measurements when introduced de novo among operators without prior ultrasound experience. Subjects and methods: This study determined intra- and interobserver variability of intrapartum ultrasound in nulliparous women in labor. Ultrasound examinations were performed independently by a midwife and a gynecologist. The symphysis–head distance (SHD) and the angle of progression (AOP) were measured by translabial ultrasound. Structured questionnaires were given to midwives and parturients. Intraclass correlation coefficient (ICC) and limits of agreement (LA) were calculated to evaluate variability. Results: A total of 33 patients were included; of whom, 28 filled in the questionnaire. A total of 19 midwives working on a delivery ward were asked to respond to the questionnaire, and 13 returned the forms. Midwives clearly continued to prefer VE over ultrasound, the majority evaluated translabial ultrasound as easy to use, but some declared to be unable to use it. The majority of patients, 71%, preferred ultrasound over VE. Reproducibility of intrapartum translabial ultrasound was good; ICC for interobserver variability was 0.603 (p=0.001) for SHD, and ICC for intraobserver variability was 0.844 (p<0.001) and 0.914 (p<0.001) for SHD and AOP, respectively. Conclusion: Patients prefer ultrasound over VE; midwives tend to stick to trusted VE. Reproducibility of intrapartum ultrasound in non-experienced operators is good. Keywords: intrapartum, ultrasound, labor